The never-ending patriarchalist plundering of Nature in Nuestra América: Theoretical approaches in the light of Eco-feminist Reflections - Arguedas-Ramírez, Rebeca (2016)
This article covers the ideas of several authors who have analyzed and generated knowledge on the subject of the colonization and new plunder of Nature as a constant from the European invasion in the fifteenth century to present day. It further mentions the characterization of ecofeminism in Latin America, Sentipensante (sensing/thinking) perspectives and theoretical paths of inspirational intuition, and sharp criticisms that are often voiceless.